Global studies encyclopedic dictionary - Chumakov, A. N.; Mazur, I. I.; Gay, William, 1949-; Howard, Michael T.; Mitrofanova, Anastasia V.; Smolkin, Vladimir M.; Branch, Jonathan P.; Gorbachev, Mikhail Sergeevich, 1931- (Value Inquiry Book Series, 2014)
This book provides brief expositions of the central concepts in the field of Global Studies. Former President of the Soviet Union Mikhail Gorbachev says, "The book is intelligent, rich in content and, I believe, necessary in our complex, turbulent, and fragile world." 300 authors from 50 countries contributed 450 entries. The contributors include scholars, researchers, and professionals in social, natural, and technological sciences. They cover globalization problems within ecology, business, economics, politics, culture, and law. This interdisciplinary collection provides a basis for understanding the concepts and methods within global studies and for accessing lengthier and more technical research in the field. The articles treat such important topics as the biosphere, ozone depletion, land resources and pollution, world health challenges, education, global modeling, sustainable development, war, weapons of mass destruction, and terrorism. The book also promotes academic cooperation, political dialogue, and mutual understanding across diverse traditions and national identities that are needed to engage successfully the many daunting challenges of globalization.